Bone Density Determination of Moose Skeletal Remains from Isle Royale National Park using Digital Image Enhancement and Quantitative Computed Tomography (QCT) - Hindelang, Mary; Maclean, Ann L. (Digital Commons @ Michigan Tech, 1997)
As part of an investigation of prey vulnerability in Isle Royale National Park, MI, digital image processing techniques were used to enhance original quantitative computed tomography (QCT) film products to detail the processes of bone resorption and reformation in skeletal remains of moose (Alces alces). Integration of these two allied imaging technologies allowed analyses of pixels representing fractions of millimetres of bone. Using regression analysis, linear conversions from the pixel digital numbers (DN) to QCT Housefield units (HU) to actual bone mineral density (BMD) values were calculated (r2=0.99), and a scale of pixels per millimetre of bone was determined. The clolour-enhanced image revealed quantifiable patterns of density, porosity and asymmetry. In addition, the procedure provided a quick but consistent methodology for evaluating numerous scans. Combining the limited use of a high-demand and expensive medical QCT scanner with a lower cost, readily available digital image processing and analysis system provides a technique for researchers to investigate the bone integrity of individual animals and populations. This method of evaluating bone density has implications for use in determining differential skeletal part-preservation in archaeofaunal studies.